2019
DOI: 10.3390/cancers11040480
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Lipidome Reorganization and Accumulation of Tissue DNA Lesions in Tumor-Bearing Mice: An Exploratory Study

Abstract: Increased rates of reactive oxygen/nitrogen species (ROS/RNS) are involved in almost all cancer types, associated with tumor development and progression, causing damage to biomolecules such as proteins, nucleic acids and membrane lipids, in different biological compartments. We used a human tumor xenograft mouse model to evaluate for the first time in parallel the remodeling of fatty acid moieties in erythrocyte membrane phospholipids and the level of ROS-induced DNA lesions in liver and kidney tissues. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 68 publications
(102 reference statements)
2
26
0
Order By: Relevance
“…Cells were lysed, genomic DNA was isolated using a high-salt extraction procedure [ 45 , 46 ] and lesions levels were quantified as described previously [ 33 , 36 , 45 , 47 , 48 ]. Briefly, 10 μg of DNA were enzymatically digested in a reaction mixture including 0.2 mM pentostatin, 5 μM BHT, 3 mM deferoxamine and the internal standards ([ 15 N 5 ]-5′ S -cdA, [ 15 N 5 ]-5′ R -cdA, [ 15 N 5 ]-5′ S -cdG, [ 15 N 5 ]-5′ R -cdG, [ 15 N 5 ]-8-oxo-dG and [ 15 N 5 ]-8-oxo-dA), the samples were filtered off by centrifugation through a 3 kDa microspin filter, cleaned up and enriched by an HPLC-UV system coupled with a sample collector and injected to the LC-MS/MS system.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were lysed, genomic DNA was isolated using a high-salt extraction procedure [ 45 , 46 ] and lesions levels were quantified as described previously [ 33 , 36 , 45 , 47 , 48 ]. Briefly, 10 μg of DNA were enzymatically digested in a reaction mixture including 0.2 mM pentostatin, 5 μM BHT, 3 mM deferoxamine and the internal standards ([ 15 N 5 ]-5′ S -cdA, [ 15 N 5 ]-5′ R -cdA, [ 15 N 5 ]-5′ S -cdG, [ 15 N 5 ]-5′ R -cdG, [ 15 N 5 ]-8-oxo-dG and [ 15 N 5 ]-8-oxo-dA), the samples were filtered off by centrifugation through a 3 kDa microspin filter, cleaned up and enriched by an HPLC-UV system coupled with a sample collector and injected to the LC-MS/MS system.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the accumulation of both the R and S diastereoisomers of cPu was followed up in organs of tumor-bearing severe combined immunodeficient (SCID) mice of different ages (4 and 17 weeks old) in comparison with the corresponding control SCID mice, providing evidence of increased oxidatively induced DNA damage occurring during tumor progression [140]. Identification and quantification by isotope dilution LC–ESI–MS/MS in two distinct tissues (the liver and kidney) revealed that tumor-bearing SCID mice had 1.1–1.4-fold higher levels of the four cyclopurines than the control SCID mice, while S -cdG was the most abundant lesion, with levels of 0.28–0.38/10 6 nucleosides in the liver and 0.24–0.25/10 6 nucleosides in the kidney, respectively (Figure 13).…”
Section: Biological Studies For Health Applicationsmentioning
confidence: 99%
“…The R / S ratios were found to be almost the same in the liver and kidney for all five experimental animal models for cdG (0.7–0.9). On the contrary, the ratio for cdA was approximately 1.3–1.9 in the kidney and 1.5–2.3 in the liver, being twice than that of cdG [140].…”
Section: Biological Studies For Health Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work done in the peculiar context of a family with gastro-intestinal and cancer disease development points attention to two non-invasive blood tests checking specific molecular indicators in two cellular compartments, in particular concerning DNA protection and cell membrane balance given by the hydrophobic fatty acid residues. The DNA-membrane correspondence has been demonstrated recently in tumor-bearing mice using purine-5',8-cyclonucleosides, as the DNA damage biomarker, together with lipidomic profiles [32], and is a promising multidisciplinary approach to cancer. PARP automodification and membrane fatty acid balance alteration checked in the family members along a time frame of more than 10 years evidenced the early response of these two indicators, with high PARP automodification and pro-inflammatory molecular profiles in apparently healthy individuals that later on developed cancer and had lethal events.…”
Section: Discussionmentioning
confidence: 99%